PENGARUH LATIHAN FISIK TERHADAP KEJADIAN INSOMNIA - Muhamad Thrisan Caecario; Muhammad Iqbal Aryahikma Trihono; Donna Adriani (Fakultas Kedokteran Universitas Trisakti, 2025)
Sleep is an essential need for humans as sufficient sleep enables individuals to perform their tasks and responsibilities effectively. Sleep disorders can disrupt physical, emotional, cognitive, and social growth. Insomnia is one of the most common sleep disorders, characterized by difficulty initiating or maintaining sleep for more than seven hours. According to the 2018 National Sleep Foundation data, the global prevalence of insomnia reached 67% among 1,507 people in Southeast Asia. In Indonesia, the prevalence of insomnia was 10% among 238 million people, with approximately 23 million individuals experiencing it. This disorder is more common in older adults, women, and those with mental health issues. People with insomnia often feel sleepy during the day, have trouble concentrating, and experience depression. Factors influencing insomnia include age, gender, family history, work environment, smoking behavior, and both mental and physical health. Exercise, including aerobic and anaerobic exercise, can affect insomnia occurrence. Structured exercise could have either positive or negative impacts on sleep quality, depending on its intensity and timing. The author hopes this study will provide further insights into the influence of physical exercise on insomnia. Conclusion: exercise performed in the morning has a positive impact on insomnia. However, if it is done at high intensity in the evening, it could increase the risk of insomnia if not properly timed. High-intensity exercise in the evening is recommended to finish 2 to 4 hours before bedtime.